Peningkatan Pengetahuan dan Keterampilan CPR dengan Pelatihan Menggunakan Bantal CPR Sebagai Media pada Remaja Pecinta Alam di Kota Lubuklinggau - Sapondra Wijaya; Wahyu Dwi Ari Wibowo; Susmini Susmini; Bambang Soewito; Rokhman Abdul (Jurnal Kesehatan, 2022)
Cardiac arrest is a direct cessation of heart function and results in death if not immediately assisted with CPR. It is necessary to increase the quantity and quality of bystander CPR through CPR education and training using reliable simulation media, one of which is the CPR pillow. This study aims to determine the effect of CPR training using a CPR pillow on the knowledge and skills of nature-lovers. This study used a quasi-experimental design with a pre and post-test approach to CPR training using a CPR pillow as a simulation medium. Samples were taken by purposive sampling technique on 40 nature-lovers. CPR knowledge was measured from knowledge about OHCA which was measured using a questionnaire. Skills were measured by the way the subject performed CPR using the CPR SOP checklist from PPNI. The results of data analysis using paired t-test showed that there was a significant effect of CPR training using the CPR Pillow on the knowledge (t=-19.891) and skills (t=-37.749) of young nature lovers with p = 0.0001. Based on the results of the analysis and discussion, it can be concluded that there is a positive influence related to CPR training using a CPR pillow on the knowledge and skills of nature-lovers about OHCA and CPR. This shows that the CPR pillow is effective for use as a community simulation medium in an effort to increase knowledge and skills in the management of OHCA.